2008
DOI: 10.1111/j.1526-4637.2008.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine Use by Primary Care Patients with Chronic Pain

Abstract: Complementary and alternative therapies were popular among patients with chronic pain disorders surveyed in academic primary care settings. When asked to choose between traditional therapies or CAM, most patients still preferred traditional therapies for pain relief. We found no association between reported CAM usage and pain severity, functional status, or self-efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
87
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 22 publications
(32 reference statements)
4
87
1
1
Order By: Relevance
“…In the previous studies, CAM therapies have shown significant results in reducing the risk of musculoskeletal and other problems in general population (20)(21)(22)(23)(24). In our study, individuals who used CAM therapies alone were less likely to report temporarily quitting work for longer than 2 months.…”
Section: Discussionmentioning
confidence: 48%
“…In the previous studies, CAM therapies have shown significant results in reducing the risk of musculoskeletal and other problems in general population (20)(21)(22)(23)(24). In our study, individuals who used CAM therapies alone were less likely to report temporarily quitting work for longer than 2 months.…”
Section: Discussionmentioning
confidence: 48%
“…Furthermore, education level of the sample might have positively affected these patients' interest in CAM. The educational attainment of SEACAP participants distinguishes this sample from those of the previous studies of CAM use among veterans [23,25] but more closely approximates education levels of civilian CAM users [6,[16][17] and of the national VA population [48].…”
Section: Discussionmentioning
confidence: 99%
“…CAM practices are becoming more widespread [2][3][4] and are most commonly used to treat musculoskeletal problems, including back and neck pain, joint pain, and arthritis [2,5]. Approximately half of civilian primary care patients with chronic pain have used at least one type of CAM treatment [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional survey [13] in academic medical centers in the United States demonstrated that 52% of primary care patients with chronic nonmalignant pain reported the current use of CAM for the relief of chronic pain. Among them, 54% agreed that nonconventional remedies helped their pain and 14% indicated that their individual alternative remedy entirely relieved their pain.…”
Section: Discussionmentioning
confidence: 99%